Scydmepitoxis gen. n., a new genus of Cyrtoscydmini (Coleoptera: Staphylinidae: Scydmaeninae) from Australia - Jałoszyński, Paweł (Zootaxa, 2014)
A new Australian genus of Cyrtoscydmini, Scydmepitoxis gen. n. with a single species S. paradoxa sp. n. is described from New South Wales. A remarkable character of the new genus is a deep sub-basal constriction of the pronotum. The morphology of Scydmepitoxis is described and illustrated in detail, and its diagnostic characters are discussed. Possible affinities with Sciacharis and Sciacharoides are suggested.